The Association between Antenatal Umbilical Cord Coiling Index Pattern and Meconium-stained Amniotic Fluid in Gestational Diabetic Mellitus - Kamolchanok Anusasananant; Sornpin Armarttasn; Budsaba Wiriyasirivaj (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective:To compare the pattern of antenatal umbilical cord coiling index (aUCI) with meconium-stained amniotic fluid in gestational diabetic mellitus (GDM) women.Materials and Methods: Gestational diabetic mellitus women between 28 weeks to 32 weeks and 6 days of gestation were included for standard ultrasonography with umbilical cord coiling measurement from a reciprocal value of the distance between a pair of coils (aUCI = 1/distance in cm). All pregnant women were divided into 2 groups (abnormal aUCI and normal aUCI) and recorded meconium-stained amniotic fluid before delivery. After delivered, total umbilical cord were measured for postpartum umbilical cord coiling index (pUCI).Results:Total of 149 GDM women, 58 women were abnormal aUCI (38.93%). The abnormal aUCI showed significantly association with meconium-stained amniotic fluid (p=0.046), low Apgar score (p=0.023) and neonatal hypoglycemia (p=0.018) when compared with normal aUCI group. The correlation of aUCI and pUCI was poor (p=0.554).Conclusion: This study showed that abnormal aUCI in GDM women was significantly associated with meconium-stained amniotic fluid. However, the aUCI had poorly correlation with pUCI.